Competition in International Voice Communications - Rossotto, Carlo Maria; Wellenius, Bjorn; Lewin, Anat; Gomez, Carlos R. (Washington, DC: World Bank, 2013)
This paper presents the case that opening international voice communication to competition is key to reform the telecommunications sector, is sustainable in developing countries, and results in major gains to consumers, businesses, and to the economy. Over the last 20 years full competition became a dominant attribute in virtually all high-income countries and in selected developing countries. Three forces were behind competition: globalization, technological change, and the emergence of international telecommunications as an enabler for integration and trade.